2011
DOI: 10.3892/mmr.2011.475
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of human papillomavirus using a PCR-restriction fragment mass polymorphism assay

Abstract: Abstract.A polymerase chain reaction-restriction fragment mass polymorphism (PCR-RFMP) assay protocol using PGMY09/11 primers for the detection and identification of human papillomavirus (HPV) has recently been developed. The present study evaluated the analytical sensitivity and clinical utility of HPV genotyping employing PCR-RFMP as compared to direct sequencing. Serial dilutions of cloned HPV DNA were analyzed in order to assess the limit of detection (LOD) and three sets of HPV clone mixtures (types 16+18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, previous studies have shown that the HC II HPV test cross-reacts with at least 15 HPV genotypes not included in its current high-risk probe cocktail set (13, 14). In this study, HPV genotypes were identified by using RFMP assay which is comparable to HC II with regard to detection of high-risk HPV infection, but is also able to identify 38 HPV genotypes in a single assay, which offers high analytical and clinical sensitivity and the advantage of reliable detection of multiple HPV infections, and it showed a good correlation with direct sequencing data (7, 9). Several studies on the prevalence of overall HPV infection in Korean women have reported rates ranging from 7.2% to 44.8%, and the prevalence of HR-HPV infection ranging from 7.2% to 34.3% (15-20).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that the HC II HPV test cross-reacts with at least 15 HPV genotypes not included in its current high-risk probe cocktail set (13, 14). In this study, HPV genotypes were identified by using RFMP assay which is comparable to HC II with regard to detection of high-risk HPV infection, but is also able to identify 38 HPV genotypes in a single assay, which offers high analytical and clinical sensitivity and the advantage of reliable detection of multiple HPV infections, and it showed a good correlation with direct sequencing data (7, 9). Several studies on the prevalence of overall HPV infection in Korean women have reported rates ranging from 7.2% to 44.8%, and the prevalence of HR-HPV infection ranging from 7.2% to 34.3% (15-20).…”
Section: Discussionmentioning
confidence: 92%
“…The restriction fragmentation mass polymorphism (RFMP) assay (GeneMetrix Co., Yongin, Korea), which utilizes PCR to amplify the HPVL1 gene followed by enzyme restriction and mass measurement using MALDI-TOF, offers a method to detect 38 types of HPV. This new method has manifested sensitivity and reliability comparable to HC II (7-9). …”
Section: Introductionmentioning
confidence: 92%